The impact of minimum acceptable and maximum probable outcomes on judgment of succes s in negotiation - Martišius, Vaclovas; Martinkevičiūtė, Sigutė (Psichologija, 1998)
The experimental data confirms viewpoint that individuals who receive the same outcome in negotiations estimate it as a relative success or failure depending on their minimum acceptable and maximum probable outcomes. The results of study also indicate that maximum probable outcome influence negotiators' feeling success more that minimum acceptable result. The interaction between minimum acceptable and maximum probable outcomes demonstrates that effects of variables on success aren't additive.
Keywords: negotiations; judgment of succes; maximum probable outcomes